Metoclopramide combined with probiotics improves gastric retention in mechanically ventilated patients following craniocerebral surgery - An, Yuling; Zhang, Baoyu; He, Qinqin; Li, Ziyu; Yi, Xiaomeng; Yi, Huimin; Wang, Hui (Frontiers in Nutrition, 2026)
ObjectivesThis study aimed to evaluate the effect of the co-administration of metoclopramide and probiotics on enteral feeding tolerance in mechanically ventilated patients after cranial surgery.MethodsFrom January 2023 to December 2024, a total of 88 patients presenting with acute brain injury and treated by craniocerebral surgery were screened. Of these, 32 were excluded and 56 patients were enrolled and assigned to either the intervention group (n = 32) or the control group (n = 24). Enteral nutrition was initiated within 24 h following nasogastric tube placement. The intervention group received a combined regimen of metoclopramide and probiotics for 3–7 days in addition to the standard enteral nutrition protocol. Feeding complications and functional outcomes were compared between the two groups.ResultsCompared to the control group, the intervention group exhibited a statistically significant reduction in total gastric residual volume (GRV) during the first 3 days of gastric tube feeding (103.1 ± 47.8 ml versus 756.3 ± 137.1 ml, P < 0.05). The intervention group demonstrated a significant reduction in vomiting and diarrhea incidence within 7 days (3.1% versus 20.8%; 6.3% versus 25%, all P < 0.05), higher serum albumin levels at 2 weeks (33.1 ± 1.5 g/L versus 31.8 ± 1.5 g/L, P < 0.05), and a shorter hospital stay (17.8 ± 4.1 days versus 23.7 ± 5.1 days, P < 0.05). However, the groups did not differ significantly in 3-month postoperative modified Rankin Scale (mRS) scores (4.2 ± 0.8 versus 4.3 ± 1.0, P > 0.05).ConclusionThe co-administration of metoclopramide and probiotics significantly reduced gastrointestinal intolerance such as gastric retention, vomiting, and diarrhea in mechanically ventilated patients following craniocerebral surgery.